(untitled) (CIPEEX, 2022)
ABSTRACT:HYDROTHERAPY IS A PHYSIOTHERAPY TECHNIQUE THAT USES THE EFFECTS OF WATER AS A THERAPEUTICRESOURCE FOR THE PREVENTION AND REHABILITATION OF PATIENTS. IT BASICALLY CONSISTS OF THE PRACTICE OFEXERCISES IN THE POOL THAT, AT APPROPRIATE TEMPERATURES, AIM TO PROMOTE FUNCTIONAL GAINS,OFFERING A BETTER QUALITY OF LIFE FOR THE PATIENT. ITS THERAPEUTIC PURPOSES ARE DIRECTLY RELATED TOBALANCE STIMULATION, REDUCING THE RISK OF FALLS, GAIT STABILITY, PROMOTING THE EFFICIENT FUNCTIONINGOF THE SOMATOSENSORY, VISUAL AND VESTIBULAR SYSTEMS. THE PRESENT STUDY AIMS TO EVALUATE THEFUNCTIONAL PERFORMANCE AND BALANCE IN THE ELDERLY WHO PRACTICE HYDROTHERAPY, IN ADDITION TOIDENTIFYING THEIR SOCIODEMOGRAPHIC PROFILE. THE METHODS USED TO CARRY OUT THIS ANALYSIS WERETHE 6-MINUTE WALK TESTS, THE BERG BALANCE SCALE AND A SOCIODEMOGRAPHIC QUESTIONNAIRE. THESTUDY IS OBSERVATIONAL, CROSS-SECTIONAL, ANALYTICAL-DESCRIPTIVE, MAKING IT POSSIBLE TO OBSERVE AFUNCTIONAL PERFORMANCE AND BALANCE OF THE ELDERLY PRACTITIONERS OF HYDROTHERAPY. THE MEAN AGEWAS 69.6 YEARS, 7 (87.5%) WERE WOMEN AND 1 (12.5%) WERE MEN. THE REFERENCE VALUES, MEANAND STANDARD DEVIATION OF THE GROUP WERE RESPECTIVELY: GLOBAL BERG BALANCE SCALE SCORE(BETWEEN 41 - 56), (52.3), (6.9); DISTANCE COVERED IN THE 3RD MINUTE OF THE WALKING TEST(219.32M), (170.6M), (66.67M); DISTANCE COVERED AT THE END OF THE WALK TEST (438.64M),(262.1M), (83, 84M). THE RESULTS OBTAINED IN THE SOCIODEMOGRAPHIC QUESTIONNAIRE DEMONSTRATETHE IMPORTANCE OF PHYSICAL ACTIVITY IN THE ELDERLY POPULATION, BOTH TO PREVENT CHANGES INBALANCE AND FUNCTIONALITY, AS WELL AS FOR PSYCHOLOGICAL AND SOCIAL WELL-BEING. FROM THEOBSERVATION OF THE ASPECTS RESEARCHED, IT IS CONSIDERED THAT THE RESULTS REACHED A GOODAVERAGE IN THE PERFORMANCE OF THE ELDERLY WHO PRACTICE HYDROTHERAPY, BECAUSE EVEN NOTREACHING ALL THE PREDICTED VALUES, THEY REMAINED WITH A GOOD GLOBAL BERG SCORE AND WITHOUTINTERCURRENCES. WE CONCLUDE, THEREFORE, THAT HYDROTHERAPY IS BENEFICIAL FOR THE ELDERLY PATIENT,SIGNIFICANTLY IMPROVING THEIR PHYSICAL, MENTAL AND SOCIAL QUALITY OF LIFE.KEY WORDS: HIDROTERAPIA; FISIOTERAPIA; IDOSOS; FUNCIONALIDADE.___________________________________________________________________________¹ PHYSIOTHERAPY STUDENT, UNIVERSIDADE EVANGÉLICA DE GOIS, CONTATORAHCHAVEIRO@GMAIL.COM.² PHYSIOTHERAPY STUDENT, UNIVERSIDADE EVANGÉLICA DE GOIS, MARIMOREIRA2019@OUTLOOK.COM.³ PHYSIOTHERAPY STUDENT, UNIVERSIDADE EVANGÉLICA DE GOIS, ISABELAROSACUNHA@GMAIL.COM.´ PHYSIOTHERAPY STUDENT, UNIVERSIDADE EVANGÉLICA DE GOIS, BRUNIKO1810@GMAIL.COM.5 PHYSIOTHERAPY TEACHER, UNIVERSIDADE EVANGÉLICA DE GOIS, DALLEYCESAR@HOTMAIL.COM.